The politics of food in the Pacific: coherence and tension in regional policies on nutrition, the food environment and non-communicable diseases. Issue 1 (12th September 2019) - Dodd, Rebecca; Reeve, Erica; Sparks, Emalie; George, Anita; Vivili, Paula; Win Tin, Si Thu; Buresova, Dai; Webster, Jacqui; Thow, Anne-Marie
Abstract: Objective: Our study analysed evolving regional commitments on food policy in the Pacific. Our aim was to understand regional priorities and the context of policy development, to identify opportunities for progress. Design: We analysed documentation from a decade of regional meetings in order to map regional policy commitments relevant to healthy diets. We focused on agriculture, education, finance, health, and trade sectors, and Heads of State forums. Drawing on relevant political science methodologies, we looked at how these sectors 'frame' the drivers of and solutions to non-communicable diseases (NCD), their policy priorities, and identified areas of coherence and tension. Setting: The Pacific has among the highest rates of non-communicable diseases in the world, but also boasts an innovative and proactive response. Heads of State have declared NCD a 'crisis' and countries have committed to specific prevention activities set out in a regional 'Roadmap'. Yet, diet-related NCD risk-factors remain stubbornly high and many countries face challenges in establishing a healthy food environment. Results: Policies to improve food environments and prevent NCD are a stated priority across regional policy forums, with clear agreement on the need for a multi-sectoral response. However, we identified challenges in sustaining these priorities as political attention fluctuated. We found examples of inconsistencies and tension in sectoral responses to the NCD epidemic that may restrict implementation of the multi-sectoral action. Conclusion: Understanding the priorities and positions underpinning sectoral responses can help drive a more coherent NCD response, and lessons from the Pacific are relevant to public health nutrition policy and practice globally.